Cationic polymer-based antimicrobial and multifunctional hydrogels for enhanced healing of infected wounds - Po, Javier Jun Fai (2018)
Hydrogel is made up of three-dimensional polymer matrix that is highly hydrophilic and can be used in many biomedical applications such as wound dressings and drug delivery. Its biocompatibility property provides a platform for research and development in antimicrobial wound dressings to treat microbial infections. Furthermore, the effectiveness of traditional wound dressings are being compromised by the increasing resistance of antibiotics and presence of leachable which affects the wound healing process. We report a wound dressing that is formulated by either ultraviolet (UV) irradiation with dextran methacrylate (Dextran MA) and UV photoinitiators or physical gelation by thermal responsive polymer pluronic and incorporated with antimicrobial polymers such as polyimidazole (PIM) or polyvinylimidazole (PVI). In vitro antibacterial test was performed to evaluate the efficacy of the different formulations of antimicrobial hydrogel samples. It was observed that PIM-Pluronic (PIM-Plu) hydrogels, formulated in 1%, 3% and 5% antimicrobial concentration, is effective in killing Methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa ER (PAER) bacteria after 4 hours of incubation. Whereas, PIM-Dextran MA (PIM-Dex) hydrogels was observed to only kill Gram-positive MRSA bacteria but not Gram-negative PAER bacteria. Further improvements such as using a stronger UV photoinitiator can aim to increase the efficacy of PIM-Dex hydrogels to Gram-negative bacteria. In the future, in vivo studies on mouse can be conducted on these antimicrobial hydrogels to better understand its efficacy on human skin.